Práticas de governança de tecnologia da informação: um estudo de caso em empresas de telecomunicações do Rio Grande do Norte - Silva, Gilson Gomes da (2009)
This study aims to understand the general model of governance of information technology adopted by telecommunication companies operating in Rio Grande do Norte. The research methodology used involved a theoretical and empirical approach prepared, involving two case studies on companies in the telecommunications industry working in the state of Rio Grande do Norte. The study covered the area of IT organizations, through interviews with managers responsible for the area of Telecommunications / IT. To study in accordance with the approach and address the problem of research, this study was based on qualitative criteria, which enabled the understanding of how companies adopt the governance of information technology. In conclusion, it was found that the governance practices of information technology employees are incipient, but that meet the needs of business and that they intend to implement in specific areas and use other practices of IT governance